APPLICATION OF LIQUID UREA FERTILIZER TO LEAVES IN OPTIMIZING VEGETATIVE LEAF GROWTH IN PLANTS THAT HAVE NOT PRODUCED IN PTPN IV REGIONAL 1 RANTAU PRAPAT GARDEN - Hartono; Badrul Ainy Dalimunthe; Fitra Syawal Harahap; Hilwa Walida (RADJA PUBLIKA, 2026)
This study aimed to determine the effect of fertilizer application with a concentration of 5 grams per liter on the vegetative growth of immature oil palm plants (TBM). The study was conducted for 4 weeks with observation intervals once a week, using two treatments: control and application of 5 grams per liter fertilizer, each with 10 replications. Observed parameters included plant height, number of leaves, stem diameter, and leaf length. Data were analyzed using ANOVA test and continued with DMRT test at the 5% level. The results showed that the application of 5 grams per liter fertilizer had a significantly different effect on all growth parameters compared to the control in each observation week. This treatment consistently resulted in higher growth, so it can be concluded that the application of 5 grams per liter fertilizer is effective in increasing the vegetative growth of immature oil palm plants.